Nanoheterostructures of Partially Oxidized RuNi Alloy as Bifunctional Electrocatalysts for Overall Water Splitting. Issue 10 (8th April 2020) - Lin, Gaoxin; Wang, Yuandong; Hong, Jinhua; Suenaga, Kazu; Liu, Lijia; Chang, Lo‐Yueh; Pao, Chih‐Wen; Zhang, Tao; Zhao, Wei; Huang, Fuqiang; Yang, Minghui; Sun, Yi‐Yang; et al.
Abstract: Electrocatalytic water splitting, as one of the most promising methods to store renewable energy generated by intermittent sources, such as solar and wind energy, has attracted tremendous attention in recent years. Developing efficient, robust, and green catalysts for the hydrogen and oxygen evolution reactions (HER and OER) is of great interest. This study concerns a facile and green approach for producing RuNi/RuNi oxide nanoheterostructures by controllable partial oxidation of RuNi nanoalloy, which is characterized and confirmed by various techniques, including high‐resolution transmission electron microscopy and synchrotron‐based X‐ray absorption spectroscopy. This nanoheterostructure demonstrates outstanding bifunctional activities for catalyzing the HER and OER with overpotentials that are both among the lowest reported values. In a practical alkali–water‐splitting electrolyzer, it also achieves a record‐low cell voltage of 1.42 V at 10 mA cm −2, which is significantly superior to the commercial RuO2 //Pt/C couple and other reported bifunctional water‐splitting electrocatalysts. Density functional theory calculations are employed to elaborate the effect of Ni incorporation. This simple catalyst preparation approach is expected to be transferrable to other electrocatalytic reactions. Abstract : RuNi rules : RuNi/RuNi oxide nanoheterostructures have been prepared as a bifunctional electrocatalyst for both the hydrogen evolution and oxygen evolution reactions in alkaline electrolyte, showing a record‐low cell voltage of 1.42 V at 10 mA cm −2 current for overall water splitting.